2020
DOI: 10.1177/0748730420929448
|View full text |Cite
|
Sign up to set email alerts
|

Are Circadian Disturbances a Core Pathophysiological Component of Schizophrenia?

Abstract: Schizophrenia is a multifactorial disorder caused by a combination of genetic variations and exposure to environmental insults. Sleep and circadian rhythm disturbances are a prominent and ubiquitous feature of many psychiatric disorders, including schizophrenia. There is growing interest in uncovering the mechanistic link between schizophrenia and circadian rhythms, which may directly affect disorder outcomes. In this review, we explore the interaction between schizophrenia and circadian rhythms from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 125 publications
0
12
0
Order By: Relevance
“…Similar to the comorbidity of sleep disruption, circadian misalignment, and psychotic and cognitive symptoms in patients [ 49 , 71 , 107 110 ], we found that circadian disruption and recognition memory impairment co-occurred in GluA1-deficient mice. Recent patient studies suggest that the extent of sleep and circadian disruption may precede the onset, as well as predict the severity, of psychotic and cognitive symptoms in clinical and healthy populations [ 108 112 ]. This raises the possibility that ameliorating sleep and circadian disruption may improve various symptoms of schizophrenia [ 113 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similar to the comorbidity of sleep disruption, circadian misalignment, and psychotic and cognitive symptoms in patients [ 49 , 71 , 107 110 ], we found that circadian disruption and recognition memory impairment co-occurred in GluA1-deficient mice. Recent patient studies suggest that the extent of sleep and circadian disruption may precede the onset, as well as predict the severity, of psychotic and cognitive symptoms in clinical and healthy populations [ 108 112 ]. This raises the possibility that ameliorating sleep and circadian disruption may improve various symptoms of schizophrenia [ 113 ].…”
Section: Discussionmentioning
confidence: 99%
“…Schizophrenia is a multifactorial disorder defined by abnormalities in one or more of five domains, namely delusions, hallucinations, disorganized thinking or speech, grossly disorganized, or abnormal motor behavior, and negative symptoms ( Arlington and Publishing, 2013 ). Circadian rhythm disruption may be a risk factor for schizophrenia by affecting the disorder onset and severity of symptoms ( Delorme et al, 2020 ). Some previous reviews have suggested little evidence linking chronotype and schizophrenia ( Ahn et al, 2008 ; Kivela et al, 2018 ; Taylor and Hasler, 2018 ).…”
Section: Association Between Chronotype and Psychiatric Disordersmentioning
confidence: 99%
“…We previously reported that circadian disruption could act as another environmental risk factor for schizophrenia ( Bhardwaj et al, 2015 ; Delorme et al, 2020 ). Circadian disruptions are disturbances of circadian rhythms, which are near 24 h endogenous rhythms governing metabolism, body temperature, hormone secretion, and many more physiological variables and systems ( Bollinger and Schibler, 2014 ).…”
mentioning
confidence: 99%